A Design and Implementation of Wireless Energy Harvesting (WEHIoT) - M, Supriya; Srinivas, Chetana (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) is an emerging computing concept that describes a structure in which everyday physical objects, each provided with unique identifiers, are connected to the Internet without requiring human interaction. Long-term and self-sustainable operation are key components for realization of such a complex network, and entail energy-aware devices that are potentially capable of harvesting their required energy from ambient sources. Among different energy harvesting methods such as vibration, light and thermal energy extraction, wireless energy harvesting (WEHIoT) has proven to be one of the most promising solutions by virtue of its simplicity, ease of implementation and availability. In this proposed project, we present an overview of enabling technologies for efficient WEHIoT, analyze the life-time of WEH-enabled IoT devices.